2013
DOI: 10.5603/cj.2013.0073
|View full text |Cite
|
Sign up to set email alerts
|

The effect of myocardial fibrosis on left ventricular torsion and twist in patients with non-ischemic dilated cardiomyopathy

Abstract: Background: Left ventricular (LV) rotation, twist, and torsion are important aspects of the cardiac performance. Myocardial fibrosis can be identified as the late gadolinium enhancement (LGE) in cardiac magnetic resonance (CMR). In this study, we investigated the association between myocardial fibrosis and LV rotational parameters in patients with nonischemic dilated cardiomyopathy (NDC (Cardiol J 2013; 20, 3: 276-286)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
1
6
0
3
Order By: Relevance
“…In dilated cardiomyopathy, twist mechanics are blunted because of the increased LV sphericity, which leads to widening of the apex and loss of the oblique architecture of the apical fibers. 35 Twist mechanics are also affected by interventions. For example, LVT improves in responders to cardiac resynchronization therapy and is predictive of post cardiac resynchronization therapy reverse remodeling.…”
Section: Lvt Mechanics In Specific Cardiac Pathologies Cardiomyopathymentioning
confidence: 99%
“…In dilated cardiomyopathy, twist mechanics are blunted because of the increased LV sphericity, which leads to widening of the apex and loss of the oblique architecture of the apical fibers. 35 Twist mechanics are also affected by interventions. For example, LVT improves in responders to cardiac resynchronization therapy and is predictive of post cardiac resynchronization therapy reverse remodeling.…”
Section: Lvt Mechanics In Specific Cardiac Pathologies Cardiomyopathymentioning
confidence: 99%
“…These may help explain why the greatest strain change occurs in the LV apex. [22][23][24] A previous study has also showed that RV function was somehow impaired in the progress of DCM. 25) RV…”
Section: Basementioning
confidence: 99%
“…Studies have shown that these indices of rotational mechanics are age dependent, exercise dependent, and preload dependent . Nevertheless, these indices were found to be outside their normal ranges in different patient populations known to have abnormal LV function: with idiopathic dilated cardiomyopathy, systemic lupus erythematosus, cirrhosis, postkidney transplant, myocardial fibrosis, postmyocardial infarction, postablation, in LV noncompaction, abnormal papillary muscle insertion, apical hypertrophic cardiomyopathy, HF with preserved ejection fraction, as well as in a normal African population . Therefore, these indices offer an additional approach to assess LV function, and the evidence that documents its advantages in a variety of clinical scenarios is rapidly growing.…”
Section: Discussionmentioning
confidence: 99%